2001
DOI: 10.4319/lo.2001.46.6.1415
|View full text |Cite
|
Sign up to set email alerts
|

The influence of particle size on seston deposition in streams

Abstract: We investigated how particle size influences deposition and transport of fine particulate organic matter in streams. Field additions of very fine (VFPOM, 15-52 m), fine (FPOM,, and medium (MPOM, 107-250 m) detritus and live diatoms (Asterionella sp.) were used to quantify the longitudinal loss rate (k P ) of each material type and to derive estimates of mean transport distance (S P ) and field deposition velocity (v dep ). In all experiments, smaller particles deposited more slowly, and thus traveled farther, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
75
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 41 publications
8
75
1
2
Order By: Relevance
“…Baseflow transport, though comprising a smaller proportion of the total load, delivers upstream POC to relatively close reaches downstream ). From measurements of particle deposition velocities (0.1 to 0.4 mm s 21 ; Thomas et al 2001), WCC mean baseflow water velocity (0.12 m s 21 ), and depth (0.10 m), we can calculate that particles travel between 31 to 124 m on average before they are deposited on the streambed. The short travel distance emphasizes the importance of local reach-scale dynamics on baseflow particle transport.…”
Section: Discussionmentioning
confidence: 99%
“…Baseflow transport, though comprising a smaller proportion of the total load, delivers upstream POC to relatively close reaches downstream ). From measurements of particle deposition velocities (0.1 to 0.4 mm s 21 ; Thomas et al 2001), WCC mean baseflow water velocity (0.12 m s 21 ), and depth (0.10 m), we can calculate that particles travel between 31 to 124 m on average before they are deposited on the streambed. The short travel distance emphasizes the importance of local reach-scale dynamics on baseflow particle transport.…”
Section: Discussionmentioning
confidence: 99%
“…Thomas et al (2001) found clear influence of fall velocity on deposition velocity for particulate organic matter and suggested that gravitational forces control the deposition for particles >100 µm. Hamm et al (2011) studied silt-sized particles in an open channel flow with permeable beds.…”
Section: Mathematical Modelling Of Suspended Sediment Transportmentioning
confidence: 99%
“…For fine material, the settling velocity will be low and the influence on the concentration distribution negligible. Thomas et al (2001) performed field measurements in two streams and found poor correlation between the calculated settling velocity and the deposition rate estimated from the collected data. Their assessment was that for sediment sizes below the range of 0.05 to 0.1 mm, gravitational effects might be small.…”
Section: Predictions By the Analytical Solutionsmentioning
confidence: 99%
“…After harvest, we measured transport distances by releasing painted corn leaves and cobs and measuring distance traveled before retention (24). We measured pollen transport during pollen shed by releasing stained corn pollen and calculating the average distance a grain traveled before settling (particle transport distance, S w ) (19,30). We estimated water transit time in the reach before pollen release by adding a solution of dissolved NaCl and following it with a conductivity meter.…”
Section: Methodsmentioning
confidence: 99%